Anticancer Activity of Holothuria Leucospilota-Derived Saponin on MKN45 Gastric Cancer Cell via Upregulation of CDH1 Hub Gene - Khadijeh Sadegh; Amirhossein Ahmadi; Ahmad Shadi; Ahmad Ghasemi (Middle East Journal of Cancer)
Background: The treatment of gastric cancer (GC) is still quite challenging. Yet, marine invertebrates have been found to produce a wide range of anticancer bioactive compounds that show promise in fighting cancer. The present study aimed to evaluate whether saponin derived from Holothuria leucospilata (H. Leucospilota), a species of sea cucumber, possesses anticancer activity against GC cells.Method: In this experimental study, the cytotoxic effect of H. Leucospilota-derived n-butanol fraction saponins (HLBS) sourced from the Persian Gulf on MKN45 GC cells was evaluated through tetrazolium salt and colony formation assays. The effect of HLBS on MKN45 cell migration, cell cycle, and apoptosis was assessed using a scratch assay, and flow cytometry, respectively. Hub genes of GC were identified through bioinformatics analysis. The effects of HLBS on the expression of the two top-ranked GC hub genes were measured using real-time polymerase chain reaction. Comparisons between groups were performed using the ANOVA test by GraphPad Prism software at the statistically significant P-value <0.05.Results: HLBS with an IC50 concentration of 75 μg/ml at 48 hours resulted in a significant decrease in cell viability, clonogenic ability (46.63% reduction, P < 0.01), and migration of MKN45 cells (74.5% reduction, P < 0.01). Moreover, HLBS led to an increase of approximately 21 and 13% in the S-phase and apoptotic cell populations, respectively. HLBS also upregulated the expression of CDH1, as a highly ranked hub gene associated with GC (P < 0.05).Conclusion: The inhibitory effect of HLBS on MKN45 cells suggests HLBS as a candidate for further drug discovery programs in GC research, and paves the way to introduce new anticancer HLBS synthetic derivatives.